Implementing Citizen Science in Primary Schools: Engaging Young Children in Monitoring Air Pollution - Castell, Nuria; Grossberndt, Sonja; Gray, Laura; Fredriksen, Mirjam F.; Skaar, Jøran S.; Høiskar, Britt Ann K. (Frontiers in Climate, 2021)
Most European cities have air pollution levels that exceed the threshold for human health protection. Children are sensitive to air pollution and thus it is important to ensure they are not exposed to high concentrations of air pollutants. In order to make a positive change towards cleaner air, a joint effort is needed, involving all civil society actors. Schools and local communities have a decisive role, and can, for example, become engaged in citizen science initiatives and knowledge coproduction. This study presents a citizen science toolbox to engage primary schools in monitoring air quality using a simple and affordable measuring method based on paper and petroleum jelly. We have developed an air meter scale making possible for the students to obtain an indicative measurement of the air pollution level. The comparison between the method against reference PM10 data collected at official air quality stations showed a good agreement, showing that the method can be used in citizen science projects. The toolbox is targeted at primary schools and children aged 6 to 12 years, although it can easily be adapted to other age groups. The main objective of the toolbox is to involve young children who are usually not targeted in air quality citizen science activities. The toolbox is designed to engage students in hands-on activities, that challenge them to create hypotheses, design scientific experiments, draw conclusions and find creative solutions to the air pollution problem. Although the main goal of the study was to provide simple but robust tools for engaging young children in air quality monitoring, we also carried out ex-ante and ex-post evaluations in 12 of the participating classes using a 10-question multiple choice test to have an indication of the contribution of the activity to knowledge integration. The results show that there is an increase in the number of correct answers, as well as a reduction in the misconceptions after conducting the activity. These results indicate that applying a citizen science approach improved science instruction and helped knowledge integration by including students’ views and taking advantage of the diverse ideas students generated.